Theoretical and methodical ground of programming of macrocycle of preparation of sportswomen, specialized in the speed-power types of track-and-field - Врублевський, Є. П. (Slobozhanskyi Herald of Science and Sport, 2011)
In this article, the methodological algorithm of development of the program of management by training process of the high-qualified sportswomen is presented. Results of research can be used in the development of the strength-and-power training system of the qualified sportswomen, a regulation of training loads taking into account biorhythmic of a female organism, optimization and an individualization of techniques and methods of diagnostics and forecasting of special working capacity in strength-and-power kinds of sports.